Review Article Factors Affecting the Occurrence of Breast Cancer Among Women in 2018 - Marsela Renasari Presty; Ismarwati Ismarwati (International Journal of Health Science and Technology, 2020)
One type of cancer with a high incidence is breast cancer and cause of death number 7 (5.7%) in Indonesia. Aim: To determine the factors affecting the occurrence of breast cancer among women. This study used literature studies from PubMed, Science Direct and ProQuest databases that are online accessed, then reviewed, analyzed and interpreted to form conclusions. The length of use of hormonal contraception, age, parity and history of cancer are not a single risk factor but there is a connection between one factor and another as a precipitating factor for the incidence of breast cancer. There is no risk factor that stands alone as a single cause. collaboration between policy makers, health workers and the community are needed to engage in further research on the other factors that can be additional risk factors and appropriate initial screening to make time and effectiveness efficient for people at high risk.